«The Philosophy of Sport» and the crisis of modern physical culture and sports world - Ібрагімов, М. М. (Slobozhanskyi Herald of Science and Sport, 2011)
Addresses issues that are associated with changes in social and philosophical paradigms of physical education and sport and their philosophical and methodological foundations of the modern era of information technology and pluralist ideologies, as well as expanded the concept of «physical training and sports science of science» and the problems of philosophy of sport to overcome the naturally arisen in this context of crisis.